Application of domestic anti-viral drug in pediatric practice - V. A. Bulgakova; O. V. Molochkova (LLC "Diagnostics and Vaccines", 2016)
The article presents the results of studies of the effectiveness and safety of domestic antiviral drug Аrbidol in children.